Five‐Step Enantioselective Synthesis of Islatravir via Asymmetric Ketone Alkynylation and an Ozonolysis Cascade. Issue 62 (1st October 2020) - Patel, Niki R.; Huffman, Mark A.; Wang, Xiao; Ding, Bangwei; McLaughlin, Mark; Newman, Justin A.; Andreani, Teresa; Maloney, Kevin M.; Johnson, Heather C.; Whittaker, Aaron M.
Abstract: A 5‐step enantioselective synthesis of the potent anti‐HIV nucleoside islatravir is reported. The highly efficient route was enabled by a novel enantioselective alkynylation of an α, β‐unsaturated ketone, a unique ozonolysis‐dealkylation cascade in water, and an enzymatic aldol‐glycosylation cascade. Abstract : Asymmetric catalysis : A 5‐step enantioselective synthesis of the potent anti‐HIV nucleoside islatravir is reported. The highly efficient route was enabled by a novel enantioselective alkynylation of an α, β‐unsaturated ketone, a unique ozonolysis‐dealkylation cascade in water, and an enzymatic aldol‐glycosylation cascade.